The association of dietary nutrients consumption with hepatic steatosis and fibrosis from NHANES 2017–2020 - Sheng, Qi; Liu, Shousheng; Yu, Haiyang; Shi, Huanchen; Xin, Yongning (Frontiers in Nutrition, 2025)
Background/objectivesHepatic steatosis and fibrosis represent significant and growing global health burdens. There is an urgent need to seek strategies for early prevention and control of hepatic steatosis and fibrosis. This study attempted to comprehensively evaluate the relationship between dietary nutrient intake and the risk of hepatic steatosis and fibrosis to provide assistance for doctors in guiding the diet of the patients.MethodsThis observational study assembled 15,560 participants from the 2017–March 2020 cohorts of the National Health and Nutrition Examination Survey. 34 nutrient intake items were included. The liver ultrasound transient elastography was used to evaluate hepatic steatosis and hepatic fibrosis. Various variables, encompassing sociodemographic characteristics, and other potential confounders were considered to ensure the stability of the findings. Additionally, the analysis accounted for various covariates and employed restricted cubic spline analysis to examine potential nonlinear relationships. Weighted quantile sum (WQS) (mixed effect) models were used in the analysis.ResultsThe negative correlations were found between low carbohydrate, vitamin C, pyridoxine, magnesium, iron and potassium intake with controlled attenuation parameter (CAP) after adjusting all the covariates and excluding non-linear correlations. Nonlinear correlation was found to exist between the consumption of energy, vitamin E, folate, sodium, alcohol, α-Linolenic acid and fish oil and hepatic steatosis (p < 0.05). The negative correlations were showed between low dietary fiber per energy and phosphorous intake with liver stiffness measurement (LSM) after adjusting all the covariates and excluding non-linear correlations (p < 0.05). High caffeine intake showed the positive correlation with LSM in Model3 after adjusting all covariates (p = 0.022). The majority of dietary nutrients intake were found to have nonlinear relationships with liver fibrosis.ConclusionOverall, many nutrient variables were newly identified associations with hepatic steatosis and fibrosis. Critical threshold intake levels were revealed that may elevate disease risk. These findings may help us better understand the complex relationship between diet and hepatic steatosis and fibrosis. Moreover, this data provides critical insights for establishing evidence-based clinical nutrition strategies to optimize the prevention and management of liver diseases.